The Relationship between Family Support and Levels of Depression with the Quality of Life of Elderly During the Pandemic Period in Pasekan Health Center, Indramayu District year 2022 - Hasim Asyari; Indra Ruswadi; Marsono (Institute of Computer Science (IOCS), 2022)
Quality elderly life is the functional condition of the elderly in optimal conditions so that they can enjoy their old age with meaning, happiness, and usefulness. This study intends to examine the association between family support and depression level and the quality of life of senior patients at the Pasekan Health Center, Indramayu Regency, during the pandemic. This study is quantitative research. The Pasekan Public Health Center, Indramayu Regency's population, consists of an average of 86 senior persons per month; therefore, a total sample is taken. The results showed: 75.6% of families supported the elderly during the pandemic, 53.5% of the elderly experienced moderate depression during the pandemic, and 59.3% of the quality of life of the elderly included moderate criteria. The statistical test for the relationship between family support and the level of depression with the quality of life of the elderly obtained a p-value of 0.000 < 0.05, which means Ho is rejected, and Ha is accepted. The conclusion is that there is a relationship between family support and the level of depression in the quality of life of the elderly during the pandemic. It should be remembered that the quality of life of the elderly has to do with family support and the level of depression. The elderly should reduce the things that can cause depression by doing regular exercise, positive thinking, and others, as well as the need for family support so that the impact on the quality of life is increasing.